Understanding EFL reading anxiety in relation to learning motivation, attitudes and strategies for Chinese and Spanish undergraduates. (August 2022) - Chen, Shifa; Du, Huinan; Wang, Shaoxin; Yang, Lianrui
Abstract: The present study explored the relationships between English as a foreign language (EFL) reading anxiety and learning motivation, attitudes, and strategies in two groups of EFL learners with different first language (L1) backgrounds. Thirty-five Chinese EFL undergraduates and thirty-seven Spanish EFL undergraduates participated in this study via a questionnaire. Quantitative analyses indicated different types of relationships between EFL reading anxiety and the abovementioned factors between these two groups of learners. While learning attitudes had a predictive effect on EFL reading anxiety for both Chinese and Spanish EFL undergraduates, the predictive effect of learning motivation and strategies were significant only among Spanish undergraduates. In addition, with learning attitudes as a mediator, learning motivation had an indirect effect on Chinese undergraduates' reading anxiety. These findings expand previous studies by exploring the relationships between EFL reading anxiety and these correlates among EFL learners with different L1 backgrounds and provide reference and basis for the intervention of FLRA throughout the language learning process.